Effectiveness of Health Education about Personal Hygiene on the Personal Hygiene Behavior of Young Women at the Darussalam Islamic Boarding School - Titik Juwariyah; Agus Priyanto; M.Khoirudin (Kirana Publisher (KNPub), 2022)
Personal hygiene is a person's efforts to maintain personal hygiene to obtain physical and psychological well-being. Personal hygiene is needed to prevent various diseases. One way to prevent the spread of disease caused by personal hygiene is by providing health education. The aimed of this research to determine the effect of health education about personal hygiene on the personal hygiene behavior of young women. The design used Quasy experimental using a one group pre-post test design approach. The sample in the research was 79 respondents taken using purposive sampling technique. Data were analyzed using the Willcoxon Signed Rank Test with significance α <0.05. The results of the study showed that before being given health education, the majority of personal hygiene behavior was adequate, 59 respondents (74.5%) and personal hygiene behavior after health education showed that almost all 71 respondents (89.8%) had good personal hygiene behavior. The results of further analysis showed that there was a significant difference in personal hygiene behavior between before and after health education (p-value=0.000; α <0.05). Health education can change respondents' behavior towards personal hygiene in young women, so it is recommended that the public pay more attention to personal hygiene to avoid various diseases, especially skin diseases.